Perbandingan Kualitas Hidup Pasien Diabetes Mellitus Tipe 2 dengan Komplikasi dan Tanpa Komplikasi - Daryaman, Usan; Amalia, Irma Nur; Jauharotun, Mia (Kisi Berkelanjutan: Sains Medis dan Kesehatan, 2025)
Introduction and Methods Diabetes mellitus is a chronic disease that can affect various organs and bodily systems over time, leading to complications. These complications may be classified as microvascular or macrovascular. Microvascular complications include neuropathy (nerve damage), nephropathy (kidney damage), and retinopathy (eye damage). Diabetes mellitus with complications can become a lifelong condition and may significantly impact the quality of life of both the individual and their family. This study aimed to examine the quality of life among type 2 diabetes mellitus patients with and without complications at Griya Antapani Primary Health Center. The study employed a quantitative, observational analytic design. A total of 56 respondents were selected through purposive sampling. Data on patients' quality of life were collected using the Diabetes Quality of Life (DQOL) instrument and an observation sheet. Data analysis was conducted using the Wilcoxon test. Results Statistical analysis using the Wilcoxon test showed a P-value of 0.032. Among the 56 respondents, 24 individuals (42.9%) had complications, while 32 individuals (57.1%) did not. Among those with complications, only 7 individuals (12.5%) reported a good quality of life, while 17 individuals (30.4%) experienced a poor quality of life. In contrast, all patients without complications (32 individuals or 57.1%) reported a good quality of life. None of the patients without complications reported a poor quality of life. Overall, 69.6% of respondents had a good quality of life, while 30.4% had a poor quality of life. Conclusion and Recommendations Patients with type 2 diabetes mellitus who experience complications tend to have a poorer quality of life compared to those without complications. The statistical analysis confirms a notable difference in the quality of life between these two groups. Future studies are encouraged to further explore the influence of patient characteristics such as age, sex, educational background, lifestyle, body mass index, and marital status, while also specifying the types of complications experienced by individuals with diabetes mellitus. Contribution to Sustainable Development Goals (SDGs) This study contributes to understanding the impact of type 2 diabetes mellitus complications on patients' quality of life. The findings support Sustainable Development Goal (SDG) 3, which aims to ensure healthy lives and promote well-being for all at all ages. Specifically, the study aligns with target 3.4: to reduce by one-third premature mortality from non-communicable diseases through prevention and treatment, and to promote mental health and well-being. This corresponds to Indonesia's national indicator 3.4.1(a), which tracks mortality due to cardiovascular disease, cancer, diabetes, or chronic respiratory diseases.